Os padrões internacionais de proteção aos direitos humanos e a reconfiguração dos direitos territoriais de povos indígenas e comunidades tradicionais no Brasil: mediações, interações e tensionamentos - Ribeiro, Inafran Francisco de Souza (2017)
The purpose of this dissertation is to understand how the process conformation process of international standards of human rights protection had repercussions on the recognition and enforcement of territorial rights of traditional peoples and communities in Brazil. From a predominantly documentary and bibliographical research we aim, with this work, to understand the historical process of conforming the international standards of protection of the human rights of indigenous and tribal peoples, focusing on the actions of States and transnationally organized civil society movements; Systematize and analyze the repercussions of the process of conforming these international standards to territorial rights in Brazil, addressing impacts on social mobilization, normative changes and the production of specific public policies; And bring to light the current challenges to the effective internalization by the Brazilian legal and political order of the international standards of protection of human rights incident on the territorial rights of traditional peoples and communities. The legal treatment given to the territorial rights of indigenous peoples was changed with the 1988 Constitution, which rejected paradigms still oriented by colonialist values aimed at the integration and cultural assimilation of these peoples. In addition, territorial rights for quilombola communities have been constitutionally recognized for the first time, and in the later decades other traditional peoples and communities that trigger specific collective identities have also become legally recognized. We argue that international standards for the protection of human rights are decisive factors of legitimation for the reconfigurations experienced by the territorial rights of these peoples in Brazil. The socialization of international standards of human rights protection fosters interactions between international and domestic political- normative systems. In the case of territorial rights, this process is made possible by the mediation exercised by intellectuals dedicated to the cause, through the circulation of ideas; By the participation of local and transnational actors of civil society, and by the articulations of the interested communities themselves.